2017
DOI: 10.3390/atmos8080154
|View full text |Cite
|
Sign up to set email alerts
|

Indian Summer Monsoon and El Niño Southern Oscillation in CMIP5 Models: A Few Areas of Agreement and Disagreement

Abstract: Using the CMIP5 model outputs, a few characteristics of Indian Summer Monsoon (ISM) rainfall and Niño 3.4 temperature are analysed during June-July-August-September (JJAS). Focusing on specified regions around central-northeast India, some general characteristic features of ISM precipitation are studied, which are shown to be varying among models. The trend of decreasing rainfall in that region as noticed in observations suggests an inconsistency among models. The ENSO also shows variation, and its phasing ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Almost all CMIP5 models suggested that EN is stronger than LN. ENSO-related various teleconnections were also investigated in many recent research using observation and CMIP5 outputs (extratropical influence: Hurtitz et al 2014; Indian Summer Monsoon (ISM): Roy and Collins 2015;Jourdain, 2013;Roy 2017; East Asian winter monsoon: Gong et al (2014Gong et al ( , 2015). This study examines Canonical and Modoki ENSO phase, focusing on CMIP5 models and observation and discusses some oceanic teleconnections.…”
mentioning
confidence: 99%
“…Almost all CMIP5 models suggested that EN is stronger than LN. ENSO-related various teleconnections were also investigated in many recent research using observation and CMIP5 outputs (extratropical influence: Hurtitz et al 2014; Indian Summer Monsoon (ISM): Roy and Collins 2015;Jourdain, 2013;Roy 2017; East Asian winter monsoon: Gong et al (2014Gong et al ( , 2015). This study examines Canonical and Modoki ENSO phase, focusing on CMIP5 models and observation and discusses some oceanic teleconnections.…”
mentioning
confidence: 99%
“…Various research (Roy 2017;Turner and Annamalai 2012;Annamalai et al 2007) explored model simulations of ISM and ENSO and discussed limitations where models disagree with observation. Here, we studied global hydrological cycle to address further on what areas models agree in general ( Fig.…”
Section: Discussion On Limitations Of Modelsmentioning
confidence: 99%
“…The ENSO can influence seasonal precipitation in various regions of the globe, and Indian summer monsoon (ISM) is one of the most crucial one (e.g. Maity and Kumar 2006;Kripalani and Kulkarni 1997;Roy 2017). It was shown that El Niño (EN) years experience less rain whereas La Niña (LN), more rainfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought years in India are usually aligned with warm ENSO or El Niño years while excess rainfall years match with La Niña. Several studies have discussed ENSO-ISM teleconnections (Turner et al, 2005;Kumar et al, 2006;Roy, 2017); moreover, few studies also detected some complementary effect on the ISM from the Indian Ocean Dipole (Ashok et al, 2001) and also from the North Atlantic Oscillation (NAO) in the previous seasons (Liu and Yanai, 2001). Such connections were shown to be sensitive to the chosen reference period of the observations (Roy and Collins, 2015).…”
mentioning
confidence: 99%